Risk of Developing Periodontitis in Patients with Primary Sjogren Syndrome: A Systematic Review - Haluanry Santoso; Idson Kamal; Rizki Amanda; Valencia Halim; Endang Winiati Bachtiar (Faculty of Dentistry, Universitas Trisakti, 2024)
Primary Sjogren syndrome (pSS) is a chronic autoimmune disorder affecting the exocrine function of the eyes and mouth. Dryness of the mouth and the underlying inflammatory condition may cause alteration of the oral microbiota and connective tissue integrity which may ultimately lead to periodontal disease, such as periodontitis. Studies have shown varying result regarding the association of periodontitis in patients with pSS. This study aims to assess the risk of developing periodontitis in patients with pSS. Literature search was conducted on PubMed, ProQuest, EBSCOHost, and Cochrane databases, with studies evaluating the risk of developing periodontitis in patients with pSS from inception to December 2023 being selected. The Newcastle-Ottawa scale was used in this study to assess the perceived risk of bias of the included studies. This review included one retrospective study and two cross-sectional studies involving 773 patients with pSS. The prevalence of periodontitis in pSS patients is 479 patients (61.9%). Inconsistency of statistical significance is found in regards of relative risk of developing periodontitis. Patients with pSS has an increased relative risk of developing periodontitis. Inconsistency of statistical significance was found between studies.